Kerjasama Imigrasi Dengan Instansi Pemerintah Dalam Penanganan Kasus Penyelundupan Manusia - Pratama Naoval Cardani Dhafasha; Anggita Ndaru Nurdiyanti; Marco Edward Pontoh (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The purpose of this study is to describe and analyze exploitative transnational crimes that are carried out directly or indirectly, with the aim of making profit for themselves and others. People smuggling is inseparable from illegal immigrants. This research method is normative-empirical qualitative in the Live Case Study group. The data collection technique used is by compiling questions and answers about Transnational Organized Crimes and compiling related literature that is still related to the titles and themes discussed in the study. The analysis of the data in this study is formed in the presentation of data (data display), data reduction (data reduction), and by drawing a conclusion. The results showed that the Directorate General of Immigration held a national coordination meeting with other government agencies such as the National Police, the Ministry of Religion, the Ministry of Manpower, and the National Agency for the Placement and Protection of Indonesian Migrant Workers (BNP2MI). OA surveillance is also carried out by the Directorate General of Immigration (Directorate General of Immigration) in collaboration with the National Police Security Intelligence Agency (Baintelkam). The formalization of this cooperation has been carried out in the form of a Cooperation Agreement. The conclusion in this study is prevention efforts, Immigration PPNS can make efforts to prevent the occurrence of people smuggling and trafficking in persons with Police Investigators, Ministry of Manpower Employment PPNS, BP2MI, Regional Governments based on Articles 56, 57, 58, 59 of Law no. 21 of 2007 concerning the Eradication of TP of Trafficking in Persons and Article 111 of Law no. 6 of 2011 concerning Immigration.